Induction of Anti-influenza Immunity by Modified Green Fluorescent Protein (GFP) Carrying Hemagglutinin-derived Epitope Structure - Inoue, Yuji (American Society for Biochemistry and Molecular Biology, 2013)
The development of vaccination methods that can overcome the emergence of new types of influenza strains caused by escape mutations is desirable to avoid future pandemics. Here, a novel type of immunogen was designed that targeted the conformation of a highly conserved region of influenza A virus hemagglutinin (HA) composed of two separate sequences that associate to form an anti-parallel β-sheet structure. Our previous study identified this β-sheet region as the structural core in the epitope of a characteristic antibody (B-1) that strongly neutralizes a wide variety of strains within the H3N2 serotype, and therefore this β-sheet region was considered a good target to induce broadly reactive immunity against the influenza A virus. To design the immunogen, residues derived from the B-1 epitope were introduced directly onto a part of enhanced green fluorescent protein (EGFP), whose surface is mostly composed of β-sheets. Through site-directed mutagenesis, several modified EGFPs with an epitope-mimicking structure embedded in their surface were prepared. Two EGFP variants, differing from wild-type (parental) EGFP by only five and nine residues, induced mice to produce antibodies that specifically bind to H3-type HA and neutralize H3N2 virus. Moreover, three of five mice immunized with each of these EGFP variants followed by a booster with equivalent mCherry variants acquired anti-viral immunity against challenge with H3N2 virus at a lethal dosage. In contrast to conventional methods, such as split HA vaccine, preparation of this type of immunogen requires less time and is therefore expected to be quickly responsive to newly emerged influenza viral strains.